PERANAN LATAR SOSIAL DALAM MENDUKUNG PENOKOHAN PADA NOVEL BATAS KARYA AKMAL NASERY BASRAL - Susanti, Hetty; Effendy, Chairil; Syam, Christanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
The study is titled The roles of social background in supporting characterizations in novel Batas by Akmal Nasery Barsal. The purpose of this research is to obtain description data about the roles of social background in supporting characterizations in novel Batas. The method in this research is descriptive method with a qualitative research, and also using literature sociology approach. The source of data in this research is novel Batas;and the data are words, phrases, and sentences in novel Batas that shows roles of social background in form of tradition, life principle, faith, and custom in supporting characterizations. The results of the research are: (1) tradition, including hunting tradition, take a bath in the river together with other members of society, plaiting anjat together, spread out sahang under the sunlight, behuma (farming), Gawai ceremony, breeding pig, the woman using kemben and fermented palm wine drinking; (2) life principle, including opinions that can be principal, guide, direction and life guide; (3) faith to God and animism; (4) Custom, including rules or daily life act, what is recognized, what is known and become a habit in society. Keywords: social background, characterizations, novel Abstrak: Penelitian ini berjudul Peranan Latar Sosial dalam Mendukung Penokohan pada Novel Batas Karya Akmal Nasery Basral. Penelitian ini bertujuan untuk memperoleh data deskripsi tentang peranan latar sosial dalam mendukung penokohan. Penelitian ini dilakukan dengan menggunakan metode deskriptif, berbentuk kualitatif. Sumber data adalah novel Batas;sedangkan datanya adalah kata, frasa, dan kalimat yang menunjukkan peranan latar sosial dalam mendukung penokohan. Hasil penelitian menunjukkan: (1) tradisi, meliputi tradisi berburu, mandi di sungai beramai-ramai, mengayam anjat beramai-ramai, menjemur sahang, behuma (berladang), upacara gawai, memelihara babi, para perempuan menggunakan kemben, dan minum tuak; (2) pandangan hidup, meliputi pendapat atau pertimbangan yang dijadikan pegangan, pedoman, arahan, dan petunjuk hidup di dunia; (3) keyakinan kepada Tuhan dan kepada roh-roh gaib; dan, (4) adat-istiadat, meliputi aturan atau perbuatan yang lazim dilakukan masyarakat, apa yang dikenal, diketahui, dan menjadi kebiasaan dalam masyarakat. Kata kunci: latar sosial, penokohan, novel.